Peningkatan Motivasi Belajar Peserta Didik Kelas X pada Materi Bersikap Kritis dan Bertanggung Jawab terhadap Media Massa dalam Pembelajaran Problem Based Learning di SMKN 1 Sewon, Yogyakarta - Yosefi Dewi Mahanani Saputra (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This research aims to improve the learning motivation of 10th-grade students at SMKN 1 Sewon Yogyakarta on the topic of being critical and responsible towards mass media through the implementation of the Problem-Based Learning (PBL) method. The teaching of Catholic Religion at this school is designed to support the school's vision of producing graduates with character and professionalism. However, student motivation in this subject remains low, as indicated by minimal participation and unsatisfactory learning outcomes. Until now, the teaching method has focused solely on textbooks without engaging variety. This study employed a Classroom Action Research (CAR) approach in two cycles, each consisting of four stages: planning, implementation, observation, and reflection. The research subjects were three 10th-grade students from the Hospitality Program. The results showed that the implementation of PBL significantly increased students' learning motivation, particularly in thinking critically and being responsible for information from mass media. In the first cycle, student motivation was still relatively low, but after improvements in the second cycle, students became more active in discussions, critical thinking, and confidently expressing their opinions. This research provides benefits for teachers to teach more effectively and is expected to positively impact the quality of education at the school. The findings also show that the PBL method helps students relate learning materials to real life, increase active engagement, and foster critical and responsible attitudes in dealing with information from the media.